Climats et pratiques de leadership dans les équipes enseignantes des écoles élémentaires - Joël Rich (Nantes Université, 2013)
The idea that the climate of the French primary schools must be carefully examined after the last publication of inquiries PISA, is henceforth imperative. The research driven here chooses to seize the nature of the relations crossed between teachers and directors/managers. Returning on the recent suggestions of the OECD to improve the functioning of schools by a better expertise of the directors/managers (Pont, Nusche, Moorman, Hopkins, 2008), the author chooses a theoretical entry connected to the recent works on the leadership and in particular to the distributed leadership (Spillane, 2008). The qualitative analysis of questionnaires shows the absence of such levels of leadership and suggests beyond, the poor organizational control of French schools as the possible limits of their efficiency.